2020
DOI: 10.1007/s13555-020-00471-y
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Manifestations, Histologic Features and Disease Progression among Cutaneous Lupus Erythematosus Subtypes: A Prospective Observational Study in Asians

Abstract: Introduction Cutaneous manifestations are central to the primary diagnosis of systemic lupus erythematosus (SLE). However, information on the clinical, histopathologic, and direct immunofluorescence (DIF) features among subtypes of cutaneous lupus erythematosus (CLE), as well as longitudinal prospective observational study to evaluate the natural history and the progression to SLE, is lacking among Asians. Our objectives are to summarize the differences in the clinical, histopathologic, and DIF ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
(63 reference statements)
2
25
0
1
Order By: Relevance
“…In our review of prior studies, the most common risk factor reported was a positive ANA (15,17,21,28,35,41). Other common risk factors included hematologic abnormalities, age at CLE onset, lupus specific antibodies like dsDNA, and mucocutaneous criteria (15,21,25,28,35,38,41). Disparities in risk factor reporting can be attributed to differences in study design, population, and methods of reporting SLE diagnosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our review of prior studies, the most common risk factor reported was a positive ANA (15,17,21,28,35,41). Other common risk factors included hematologic abnormalities, age at CLE onset, lupus specific antibodies like dsDNA, and mucocutaneous criteria (15,21,25,28,35,38,41). Disparities in risk factor reporting can be attributed to differences in study design, population, and methods of reporting SLE diagnosis.…”
Section: Discussionmentioning
confidence: 94%
“…Four studies pre-dated the development of the 1982 ACR criteria and used ARA criteria ( 25 , 27 , 28 , 33 ). Two studies used the 2012 SLICC classification criteria ( 21 , 31 ). None have employed the 2019 EULAR/ACR criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our case and a previously reported case have brought attention to the association between scalp involvement of PDP and the development of scarring alopecia. Regarding histopathological features of our case, we theorize that the mechanism may involve the compression of hair follicles by surrounding thickening connective tissues and extracellular matrix, leading to follicular degeneration and further develop scarring alopecia [8][9][10][11][12].…”
Section: Answermentioning
confidence: 89%
“…Histopathological examination can be an alternative diagnostic tool to differentiate between various types of CLE, while serology profile has been identified as a marker of systemic involvement of CLE. 14…”
Section: Discussionmentioning
confidence: 99%